Stabilization of laminated beams with interfacial slip - Assane Lo; Nasser-eddine Tatar (Electronic Journal of Differential Equations, 2015)
We study a laminated beam consisting of two identical beams of uniform thickness, which is modeled as Timoshenko beams. An adhesive of small thickness is bonding the two layers and creating a restoring force producing a damping. It has been shown that the interfacial slip between the layers alone is not enough to stabilize the system exponentially to its equilibrium state. Some boundary control has been used in the literature for that purpose. In this paper, we show that for viscoelastic material there is no need for any kind of internal or boundary control.